PSMA targeted conjugates based on dextran - Janczewska, Magdalena; Szkop, Michał; Pikus, Grzegorz; Kopyra, Konstancja; Świątkowska, Anna; Brygoła, Kamil; Karczmarczyk, Urszula; Walczak, Jarosław; Żuk, Michał Tomasz; Duszak, Jolanta; Ciach, Tomasz (Applied radiation and isotopes, 2021)
Currently, radiotherapy is one of the most popular choices in clinical practice for the treatment of cancers. While it offers a fantastic means to selectively kill cancer cells, it can come with a host of side effects. To minimize such side effects, and maximize the therapeutic effect of the treatment, we propose the use of targeted radiopharmaceuticals. In the study presented herein, we investigate two synthetic pathways of dextran-based radiocarriers and provide their key chemical and physical properties: stability of the bonding of chelating agent and tertiary structure of obtained formulations and its influence on biological properties. Additionally, PSMA small molecule inhibitor was attached and quantified using DELFIA fluorescence assay. Finally, biological properties and radiolabeling yield were studied using confocal microscopy and ITLC-SG chromatography. Two types of Dex-conjugates – micelle-like nanoparticles (NPs) and non-folded conjugates – were successfully generated and shown to exhibit cellular effects. The tertiary structure of the conjugates was found to influence the selectivity of PSMA and mediate cell binding as well as cellular uptake mechanisms. NPs were shown to be internalized by other, non – PSMA mediated channels. Simultaneously, the uptake of non-folded conjugates required PSMA inhibitor to pass through cell membrane. The radiochemical yield of NHS coupled DOTA chelator was between 91.3 and 97.7% while the TCT-amine bonding showed higher stability and gave the yields of 99.8–100%. We obtained novel, dextran-based radioconjugates, and presented a superior method of chelator binding, resulting in exquisite radiochemical properties as well as selective cross-membrane transport. •Two synthetic pathways of dextran based radiocarriers.•Highly stable linkage between DOTA chelator and the dextran chain.•Role of the tertiary structure in the receptor specific cellular uptake.